Derivations of evolution algebras associated to graphs over a field of any characteristic. Issue 15 (13th October 2022) - Reis, Tiago; Cadavid, Paula
Abstract : The space of derivations of finite dimensional evolution algebras associated to graphs over a field with characteristic zero has been completely characterized in the literature. In this work we generalize that characterization by describing the derivations of this class of algebras for fields of any characteristic.